Stock market impact of visual and verbal clues from bank CEO interviews on CNBC during financial crisis - Fam, Suen Li (2013)
This paper investigates how media exposure of CEO via CNBC interviews affects investors’ response and trading behavior during the 08/09 financial crisis period. It had been proven that media coverage is endogenous, and hence we assume that CEOs bears specific intentions for their media appearance. When the financial markets are suffering and panicking during the crisis, one of the intentions of CEO interviews would be to reduce investors’ uncertainty, thereby increasing the company’s stock price and reducing price volatility (perceived risk level).